Optical detection of di- and triphosphate anions with mixed monolayer-protected gold nanoparticles containing zinc(II)–dipicolylamine complexes - Reinke, Lena; Bartl, Julia; Koch, Marcus; Kubik, Stefan (Beilstein Journal of Organic Chemistry, 2020)
Gold nanoparticles covered with a mixture of ligands of which one type contains solubilizing triethylene glycol residues and the other peripheral zinc(II)–dipicolylamine (DPA) complexes allowed the optical detection of hydrogenphosphate, diphosphate, and triphosphate anions in water/methanol 1:2 (v/v). These anions caused the bright red solutions of the nanoparticles to change their color because of nanoparticle aggregation followed by precipitation, whereas halides or oxoanions such as sulfate, nitrate, or carbonate produced no effect. The sensitivity of phosphate sensing depended on the nature of the anion, with diphosphate and triphosphate inducing visual changes at significantly lower concentrations than hydrogenphosphate. In addition, the sensing sensitivity was also affected by the ratio of the ligands on the nanoparticle surface, decreasing as the number of immobilized zinc(II)–dipicolylamine groups increased. A nanoparticle containing a 9:1 ratio of the solubilizing and the anion-binding ligand showed a color change at diphosphate and triphosphate concentrations as low as 10 μmol/L, for example, and precipitated at slightly higher concentrations. Hydrogenphosphate induced a nanoparticle precipitation only at a concentration of ca. 400 μmol/L, at which the precipitates formed in the presence of diphosphates and triphosphates redissolved. A nanoparticle containing fewer binding sites was more sensitive, while increasing the relative number of zinc(II)–dipicolylamine complexes beyond 25% had a negative impact on the limit of detection and the optical response. Transmission electron microscopy provided evidence that the changes of the nanoparticle properties observed in the presence of the phosphates were due to a nanoparticle crosslinking, consistent with the preferred binding mode of zinc(II)–dipicolylamine complexes with phosphate anions which involves binding of the anion between two metal centers. This work thus provided information on how the behavior of mixed monolayer-protected gold nanoparticles is affected by multivalent interactions, at the same time introducing a method to assess whether certain biologically relevant anions are present in an aqueous solution within a specific concentration range.
Keywords: chemosensor; diphosphate; gold nanoparticles; optical sensing; triphosphate

(untitled) - Shenhar, R.; Rotello, V. M. (Acc. Chem. Res., 2003)

(untitled) - Giljohann, D. A.; Seferos, D. S.; Daniel, W. L.; Massich, M. D.; Patel, P. C.; Mirkin, C. A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Saha, K.; Agasti, S. S.; Kim, C.; Li, X.; Rotello, V. M. (Chem. Rev., 2012)

(untitled) - Sabela, M.; Balme, S.; Bechelany, M.; Janot, J.-M.; Bisetty, K. (Adv. Eng. Mater., 2017)

(untitled) - Du, J.; Zhu, B.; Peng, X.; Chen, X. (Small, 2014)

(untitled) - Chang, C.-C.; Chen, C.-P.; Wu, T.-H.; Yang, C.-H.; Lin, C.-W.; Chen, C.-Y. (Nanomaterials, 2019)

(untitled) - Ghosh, S. K.; Pal, T. (Chem. Rev., 2007)

(untitled) - Halas, N. J.; Lal, S.; Chang, W.-S.; Link, S.; Nordlander, P. (Chem. Rev., 2011)

(untitled) - Amendola, V.; Pilot, R.; Frasconi, M.; Maragò, O. M.; Iatì, M. A. (J. Phys.: Condens. Matter, 2017)

(untitled) - Elghanian, R.; Storhoff, J. J.; Mucic, R. C.; Letsinger, R. L.; Mirkin, C. A. (Science, 1997)

(untitled) - Kim, Y.; Johnson, R. C.; Hupp, J. T. (Nano Lett., 2001)

(untitled) - Lin, S.-Y.; Liu, S.-W.; Lin, C.-M.; Chen, C.-h. (Anal. Chem. (Washington, DC, U. S.), 2002)

(untitled) - Vilela, D.; González, M. C.; Escarpa, A. (Anal. Chim. Acta, 2012)

(untitled) - Wang, C.; Yu, C. (Rev. Anal. Chem., 2013)

(untitled) - Wilson, R. (Chem. Soc. Rev., 2008)

(untitled) - Sokkalingam, P.; Hong, S.-J.; Aydogan, A.; Sessler, J. L.; Lee, C.-H. (Chem. – Eur. J., 2013)

(untitled) - Aydogan, A.; Lee, G.; Lee, C.-H.; Sessler, J. L. (Chem. – Eur. J., 2015)

(untitled) - Bartl, J.; Reinke, L.; Koch, M.; Kubik, S. (Chem. Commun., 2020)

(untitled) - Hunter, C. A.; Anderson, H. L. (Angew. Chem., Int. Ed., 2009)

(untitled) - Fasting, C.; Schalley, C. A.; Weber, M.; Seitz, O.; Hecht, S.; Koksch, B.; Dernedde, J.; Graf, C.; Knapp, E.-W.; Haag, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - von Krbek, L. K. S.; Schalley, C. A.; Thordarson, P. (Chem. Soc. Rev., 2017)

(untitled) - Kim, S. K.; Lee, D. H.; Hong, J.-I.; Yoon, J. (Acc. Chem. Res., 2009)

(untitled) - Sakamoto, T.; Ojida, A.; Hamachi, I. (Chem. Commun., 2009)

(untitled) - Ngo, H. T.; Liu, X.; Jolliffe, K. A. (Chem. Soc. Rev., 2012)

(untitled) - Lee, S.; Yuen, K. K. Y.; Jolliffe, K. A.; Yoon, J. (Chem. Soc. Rev., 2015)

(untitled) - Jolliffe, K. A. (Acc. Chem. Res., 2017)

(untitled) - Skinner, A. V.; Han, S.; Balasubramanian, R. (Sens. Actuators, B, 2017)

(untitled) - Beyeh, N. K.; Díez, I.; Taimoory, S. M.; Meister, D.; Feig, A. I.; Trant, J. F.; Ras, R. H. A.; Rissanen, K. (Chem. Sci., 2018)

(untitled) - Sánchez, G.; Curiel, D.; Tatkiewcz, W.; Ratera, I.; Tárraga, A.; Veciana, J.; Molina, P. (Chem. Sci., 2014)

(untitled) - Oh, D. J.; Kim, K. M.; Ahn, K. H. (Chem. – Asian J., 2011)

(untitled) - Kim, S.; Eom, M. S.; Kim, S. K.; Seo, S. H.; Han, M. S. (Chem. Commun., 2013)

(untitled) - Kim, S.; Eom, M. S.; Seo, S. H.; Han, M. S. (Tetrahedron Lett., 2013)

(untitled) - Kim, S.; Eom, M. S.; Yoo, S.; Han, M. S. (Tetrahedron Lett., 2015)

(untitled) - Li, D. X.; Zhang, J. F.; Jang, Y. H.; Jang, Y. J.; Kim, D. H.; Kim, J. S. (Small, 2012)

Biological Role of Inorganic Pyrophosphate - Heinonen, J. K. (Kluwer Acacemic Publishers, 2001)

(untitled) - Hargrove, A. E.; Nieto, S.; Zhang, T.; Sessler, J. L.; Anslyn, E. V. (Chem. Rev., 2011)

(untitled) - Mei, B. C.; Susumu, K.; Medintz, I. L.; Delehanty, J. B.; Mountziaris, T. J.; Mattoussi, H. (J. Mater. Chem., 2008)

(untitled) - Susumu, K.; Oh, E.; Delehanty, J. B.; Blanco-Canosa, J. B.; Johnson, B. J.; Jain, V.; Hervey, W. J., IV; Algar, W. R.; Boeneman, K.; Dawson, P. E.; Medintz, I. L. (J. Am. Chem. Soc., 2011)

(untitled) - Oh, E.; Delehanty, J. B.; Klug, C. A.; Susumu, K.; Algar, W. R.; Goswami, R.; Medintz, I. L. (Chem. Commun., 2018)

(untitled) - Ojea-Jiménez, I.; Bastús, N. G.; Puntes, V. (J. Phys. Chem. C, 2011)

(untitled) - Sebby, K. B.; Mansfield, E. (Anal. Bioanal. Chem., 2015)

(untitled) - Rostek, A.; Mahl, D.; Epple, M. (J. Nanopart. Res., 2011)

(untitled) - Edgar, W. M.; Jenkins, G. N. (Arch. Oral Biol., 1972)

(untitled) - Shao, N.; Wang, H.; Gao, X.; Yang, R.; Chan, W. (Anal. Chem. (Washington, DC, U. S.), 2010)

(untitled) - Ryan, L. M.; Kozin, F.; Mccarty, D. J. (Arthritis Rheum., 1979)

(untitled) - Schmuck, C. (Coord. Chem. Rev., 2006)

(untitled) - Schmuck, C.; Wich, P. (Top. Curr. Chem., 2007)

(untitled) - He, H.; Ostwaldt, J.-E.; Hirschhäuser, C.; Schmuck, C.; Niemeyer, J. (Small, 2020)